Aetiology and comorbidities of cerebral palsy in a developing country - Eyong, Komomo I.; Asindi, Asindi A.; Torty, Chimaeze (International Journal of Research in Medical Sciences, 2018)
Background: Cerebral palsy (CP) is a common disabling condition of movement and posture causing activity limitation arising from a static injury to the developing brain. Common risk factors for cerebral palsy in Africa include severe birth asphyxia, kernicterus and neonatal infections. This study is aimed at determining the aetiology and comorbidities associated with cerebral palsy in our environment. Methods: All children with CP presenting to the Paediatric Neurology clinic of the University of Calabar Teaching Hospital whose parent gave consent were recruited into the study. The biodata of the children and that of the parent’s/ care givers were obtained. A detailed pregnancy and delivery history, neonatal history, seizures during first three years of life and developmental mile stones was documented. Results: Seventy children with CP were recruited into the study of which 46 (65.7%) were males and 24 (34.3%) females. Majority of the children were from low social class and products of home, church or TBA’S delivery where supervision is poor. Severe birth asphyxia and CNS infections are the commonest identified risk factors. Spastic quadriplegic CP is the dominant type of CP followed by spastic hemiplegia. There is a significant statistical relationship between the aetiology and the type of CP. Epilepsy (60%) speech defect (42.9%) and microcephaly (40%) are the predominant comorbidities seen in the study. Cortical atrophy and ventricular dilatation are predominant CT findings in contrast to periventricular leukomalecia seen in developed countries. Conclusions: Majority of the patients with CP in this study are from low social class and were delivered in places with poor obstetrics care. Improved perinatal care through an adequate social support system may reduce the burden of the disease.